A cadmium(II)-based coordination compound constructed from 1-(tetrazo-5-yl)-4-(triazo-1-yl)benzene for highly selective luminescence sensing of acetone, Fe3+ and Cr2O72- ions. Issue 4 (14th March 2022) - Hu, Dou-Dou; Wang, Jun-Jie; Cao, Meng-Ge; Hu, Bing-Qing; Lin, Qian-Wen; He, Yu-Fei; Fu, Yi-Ran; Li, Chao-Yang; Li, Ji-Xiang; Wang, Xin-Fang
Abstract: A Cd(ΙI)-based luminescent coordination polymer, namely [Cd(L)2 (H2 O)2 ]n (1 ), has been synthesized by 1-(tetrazo-5-yl)-4-(triazo-1-yl)benzene ligand (HL) and structurally characterized. The selective luminescence sensing performances of 1 were systematically studied. Interestingly, it can sensitively detect trace amounts of acetone, Fe 3+ and Cr2 O7 2- ions through luminescence quenching, respectively. Graphical Abstract: UF0001